IMPORTED MALARIA ON THE TERRITORY OF BELGRADE FROM 2014 TO 2018 - Giljaca, Sonja; Maris, Slavica (HEALTH CARE, 2020)
Introduction/Aim: In the former Yugoslavia, malaria eradication was officially confirmed by the World Health Organization in 1974. Since then, only imported cases of malaria have been recorded in Serbia. The aim of this study was to analyze epidemiological characteristics of imported malaria on the territory of Belgrade from 2014 to 2018.Methods: A descriptive epidemiological study was applied. Data on the number of newly diagnosed patients with imported malaria by gender, age and region from which malaria was imported, for the specified period were taken from the Institute of Public Health of Belgrade. Proportional, crude and age-specific incidence rates were used in the data analysis.Results: There were 77 cases of imported malaria registered on the territory of Belgrade from 2014 to 2018, and the average crude incidence rate was 0.9/100,000. The highest number of patients (28) and the highest incidence rate (1.7/100,000) of imported malaria were registered in 2017, and the lowest number of patients (7) and the lowest incidence rate (0.4/100,000) were registered in 2014 and 2018. This disease was more common among men (89.6%) than among women (10.4%). The highest age-specific rate of imported malaria was registered in the age group of 10-19 years (3.5/100,000). P. vivax (45.4%) and P. falciparum (37.7%) were the most frequent causative agents of imported malaria in Belgrade. About 88% of imported malaria cases were from people living in endemic areas of Asia and Africa. The largest number of newly diseased cases of imported malaria stated migration (44.2%) and work (39.0%) as the reason for their stay in endemic regions. The condition is registered throughout the year, with the peak of the disease in August (19.5%).Conclusion: It is necessary to continuously improve the health education of the population, in order to educate population about the manner of transmission of malaria, and to apply measures of prevention during their stay in endemic countries.
Keywords: imported malaria, incidence, endemic regions